الإمام الباقلاني والنصرانية : دراسة في كتابه "تمهيد الأوائل وتلخيص الدلائل" - Idris Ismail (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 1999)
This study analyses the treatises of al-Imam Abu Bakr Muhammad Ibn al-Tayyib al-Baqillani (d. 403H / 1013 A.D) about Christianity. In particular, this study attempts to evaluate the writings of al-Imam al-Baqillani on and his refutations of Christian beliefs, with special reference to his book: Tamhid al-Awa'il wa Talkhis al-Dala'il which contains basic elements of Christian beliefs, such as the issue of jawhar (essence), trinity, incarnation and the festivals which they adopted from the Byzantian polytheist heritage. In addition, the study compares the method used by al-Imam al-Baqillani and the methods which were used by other Muslim scholars in refuting the Christian beliefs during his time. Finally, the study examines how far al-Baqillani's treatises influenced the contemporary Muslim-Christian dialogue. Al-Imam al-Baqillani was one of the pioneers who used logic and philosophy to refute the Christian beliefs and values. He is regarded as one of the Muslim scholars who was well versed in Islamic theology, comparative religion and other Islamic sciences. Thus, the modern researchers should benefit from his efforts to argue with the Christians.